The Information in Hedge Fund Option Holdings - Anand, Amber; Hua, Jian; Puckett, Andy (Management Science, 2024)
We provide new insights on how hedge funds use options and short-selling channels to trade on their negative information. Bearish information in hedge fund option positions is economically large, distinct from information in short interest, and it is the combination of option positions and short interest that provides the strongest information signal. A portfolio of stocks with high short interest and bearish hedge fund option positions predicts negative abnormal returns that are more than four times as large as the portfolio with high short interest and bullish options positions. The information in hedge fund option positions increases during periods of market stress, whereas that in short interest does not. This increase is concentrated in capital-constrained hedge funds, suggesting that options provide a channel for capital-constrained hedge funds to exploit their information advantage. This paper was accepted by Lukas Schmid, finance. Funding: J. Hua received support for this project from a PSC-CUNY Award, jointly funded by The Professional Staff Congress and The City University of New York. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2023.4785 .